Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects. (April 2023) - Yuan, Fang-Yu; Tang, Zhuo-Ya; Yan, Xue-Long; Huang, Dong; Weng, Han-Zhuang; Huang, Jia-Luo; Fan, Run-Zhu; Chen, Ye; Yin, Sheng; Tang, Gui-Hua
Abstract: Chromatographic fractionation of the 95% EtOH extract of the roots of Stellera chamaejasme yielded 20 sesquiterpenoids of four different types, guaiane-, carotane-, sesquicarane-, and alpiniane-types. Among them, sesquistrachanoids A−F were previously undescribed ones, whose structures including absolute configurations were elucidated by spectroscopic methods, the Mo2 (OAc)4 -induced ECD experiment, and analysis of experimental and calculated 1D NMR and ECD data. Sesquistrachanoid A is a 2, 3- seco -guaiane-type sesquiterpenoid with a α -pyrone core and sesquistrachanoid B is the first example of 8, 9- seco -guaiane-type sesquiterpenoid featured with an 1, 8- δ -lactone core. Sesquistrachanoid C is a guaiane sesquiterpenoid characterized by a peroxide bridge between C-8 and C-10. All sesquiterpenoids were evaluated for their neuroprotective effects on cell damage induced by sodium nitroprusside in PC-12 cells. The bioassay results showed that six compounds at 10 μM could restore the cell viability, being comparable to that of the positive control edaravone. The mechanistic study on the most pronounced activity compound, stelleraguaianone B, demonstrated that it played a neuroprotective role by promoting the mRNA expression of antioxidant enzymes to reduce oxidative stress. Graphical abstract: Six undescribed sesquiterpenoids and 14 known ones were isolated from the roots of Stellera chamaejasme . Stelleraguaianone B (11 ) played a neuroprotective role by promoting the mRNA expression of antioxidant enzymes to reduce oxidative stress. Image 1 Highlights: Six undescribed sesquiterpenoids and 14 known ones were isolated from Stellera chamaejasme. Sesquistrachanoid A is a 2, 3- seco -guaiane with a α -pyrone core. Sesquistrachanoid B is the first example of 8, 9- seco -guaiane featured with an 1, 8- δ -lactone core. Sesquistrachanoid C is characterized by a peroxide bridge between C-8 and C-10. Stelleraguaianone B showed the most pronounced neuroprotective activity.